Efektivitas Media Smart Box dalam Mengembangkan Kemampuan Kognitif Anak Usia 5–6 Tahun di Taman kanak-kanak Kemala Bhayangkari 1 Kota Padang - Ummi Zakia; Serli Marlina (STKIP Subang, 2026)
ABSTRACK Cognitive ability is one aspect of development that is very important to be stimulated from an early age because it plays a role in forming the ability to think, understand information, and solve various situations faced by children. However, in learning practices, the use of media is still found to be less varied so that the stimulation of children's cognitive abilities has not developed optimally. This study aims to determine the effectiveness of using Smart Box media in developing the cognitive abilities of children aged 5-6 years at Kemala Bhayangkari 1 Kindergarten, Padang City. This study uses a quantitative approach with a pre-experimental method through a One Group Pretest-Posttest Design. The research subjects were 16 children in group B3. The data collection technique used a test instrument consisting of five indicators of cognitive abilities. Data analysis was carried out using a normality test and a paired sample t-test hypothesis test with the help of SPSS version 27. The results of the study showed an increase in children's cognitive abilities after participating in learning using Smart Box media. The average pretest score of 6 increased to 14.13 in the posttest. The paired sample t-test results showed a significance value of 0.001 < 0.05, indicating a significant difference between children's abilities before and after treatment. Thus, the Smart Box media has proven effective in developing the cognitive abilities of 5–6-year-old children at Kemala Bhayangkari 1 Kindergarten in Padang City.